Casein Kinase 1δ/ε Inhibitor, PF670462 Attenuates the Fibrogenic Effects of Transforming Growth Factor-β in Pulmonary Fibrosis - Keenan, Christine R.; Langenbach, Shenna Y.; Jativa, Fernando; Harris, Trudi; Li, Meina; Chen, Qianyu; Xia, Yuxiu; Gao, Bryan; Schuliga, Michael J.; Jaffar, Jade; Prodanovic, Danica; Tu, Yan; et al. (Frontiers in Pharmacology, 2018)
Transforming growth factor-beta (TGF-β) is a major mediator of fibrotic diseases, including idiopathic pulmonary fibrosis (IPF). However, therapeutic global inhibition of TGF-β is limited by unwanted immunosuppression and mitral valve defects. We performed an extensive literature search to uncover a little-known connection between TGF-β signalling and casein kinase (CK) activity. We have examined the abundance of CK1 delta and epsilon (CK1δ/ε) in lung tissue from IPF patients and non-diseased controls, and investigated whether inhibition of CK1δ/ε with PF670462 inhibits pulmonary fibrosis. CK1δ/ε levels in lung tissue from IPF patients and non-diseased controls were assessed by immunohistochemistry. Anti-fibrotic effects of the CK1δ/ε inhibitor PF670462 were assessed in pre-clinical models, including acute and chronic bleomycin mouse models and in vitro experiments on spheroids made from primary human lung fibroblast cells from IPF and control donors, and human A549 alveolar-like adenocarcinoma-derived epithelial cells. Increased expression of CK1δ and ε in IPF lungs compared to non-diseased controls was accompanied by increased levels of the product, phospho-period 2. In vitro, PF670462 prevented TGF-beta-induced epithelial-mesenchymal transition. The stiffness of IPF-derived spheroids was reduced by PF670462 and TGF-beta induced fibrogenic gene expression was inhibited. The CK1δ/ε inhibitor PF670462 administered systemically or locally by inhalation prevented both acute and chronic bleomycin-induced pulmonary fibrosis in mice. PF670462 administered in a ‘therapeutic’ regimen (day 7 onwards) prevented bleomycin-induced lung collagen accumulation. Elevated expression and activity of CK1 δ and ε in IPF and anti-fibrogenic effects of the dual CKTransforming growth factor-beta (TGF-β) is a major mediator of fibrotic diseases, including idiopathic pulmonary fibrosis (IPF). However, therapeutic global inhibition of TGF-β is limited by unwanted immunosuppression and mitral valve defects. We performed an extensive literature search to uncover a little-known connection between TGF-β signalling and casein kinase (CK) activity. We have examined the abundance of CK1 delta and epsilon (CK1δ/ε) in lung tissue from IPF patients and non-diseased controls, and investigated whether inhibition of CK1δ/ε with PF670462 inhibits pulmonary fibrosis. CK1δ/ε levels in lung tissue from IPF patients and non-diseased controls were assessed by immunohistochemistry. Anti-fibrotic effects of the CK1δ/ε inhibitor PF670462 were assessed in pre-clinical models, including acute and chronic